Acclimatization strategies--preparing for exercise in the heat - Shapiro, Y.; Moran, D.; Epstein, Y. (International Journal of Sports Medicine, 1998)
More than 200 years ago, in 1768, Lind in his monograph: "An assay on diseases incidental to Europeans in hot climate" pointed out that habituation to hot climates reduced the danger to health. Two centuries later, Lind and Bass in a classical study which was carried out under hot/dry climatic conditions (49 degrees C and 20% rh) demonstrated that the adaptation to heat may be described as the series of physiological adjustments that occur when a person who is accustomed of living in a cool environment is transferred to a hot climate. This adaptation is a process which is fully achieved after 10 to 14 days of exposure to heat, but two thirds or even 75% of the adaptation is obtained already within 5 days (1). According to this study improved tolerance to heat is related to typical physiological changes: heightened sweating response, lowered heart rate, and lowered rectal temperature during exercise in the heat.